Comparison of Pericanalicular and Intracanalicular Fibroadenoma Mammae Growth Pattern on Various Age Range - Utamie, Hilda Maulyda; Ningrom, Ira Citra; Handoyo Sakti, Yuhantoro Budi; Maulana, Andi Muh. (Universitas Muhammadiyah Semarang, 2023)
Background: Fibroadenoma mammae is the most common type of benign breast tumor in women. Fibroadenoma mammae can occur on various ages, there is no much data recorded about anatomical pathology especially regarding the distribution of fibroadenoma mammae growth pattern in Siaga Medika Purbalingga Hospital. Study in Indonesia that focus on this topic also remain scarce.Objective: To analyze comparison between the growth pattern in fibroadenoma mammae patients with age range 11-50 years.Method: This cross-sectional study with data collected restrospectively based on medical records and histopatological examination in Siaga Medika Purbalingga Hospital. Statistical analysis was done using JASP 0.14.1.0.Results: The majority of patients with fibroadenoma mammae were in the age range 21-30 years (48.9%) with pericanalicular pattern (66%). The four groups had different two growth pattern (p <0.001). Odds ratio showed 3.4 that means patient with age ≤30 years has chance 3.4x to diagnose with pericanalicular fibroadenoma mammae than patient with age >30 years.Conclusion: Incidence of pericanalicular and intracanalicular fibroadenoma mammae growth pattern in Siaga Medika Purbalingga Hospital patients can be affected by age.